2022
DOI: 10.1029/2021gl097647
|View full text |Cite
|
Sign up to set email alerts
|

Phase Coherence Between Surrounding Oceans Enhances Precipitation Shortages in Northeast Brazil

Abstract: Understanding the direct and indirect impact of the Pacific and Atlantic Oceans on precipitation in the region of Northeast Brazil (NEB) is crucial for monitoring unprecedented drought events. We propose nonlinear methods of phase coherence and generalized event synchronization analysis to understand the underlying mechanism. In particular, the relationships between sea surface temperature (SST) variability and the standard precipitation index are interpreted as direct interactions, while the relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…Drought events were observed during El Ninho (1998, 2002, and 2015-2016), La Nina (2011-2012), and the 2012-2018 drought was related to a warmer tropical North Atlantic (and reinforced by an El Nino event in 2016) [21,26]. A recent study based on the nonlinear phase coherence and event synchronization analysis of sea surface temperature (SST) in the North Atlantic and Pacific oceans and the standardized precipitation index (SPI) in the NEB showed that tropical North Atlantic plays the dominant role for precipitation variability and that the indirect Pacific-North Atlantic phase synchronizations have a significant influence on the development and reinforcement of the droughts in the NEB [27].…”
Section: Introductionmentioning
confidence: 99%
“…Drought events were observed during El Ninho (1998, 2002, and 2015-2016), La Nina (2011-2012), and the 2012-2018 drought was related to a warmer tropical North Atlantic (and reinforced by an El Nino event in 2016) [21,26]. A recent study based on the nonlinear phase coherence and event synchronization analysis of sea surface temperature (SST) in the North Atlantic and Pacific oceans and the standardized precipitation index (SPI) in the NEB showed that tropical North Atlantic plays the dominant role for precipitation variability and that the indirect Pacific-North Atlantic phase synchronizations have a significant influence on the development and reinforcement of the droughts in the NEB [27].…”
Section: Introductionmentioning
confidence: 99%
“…A região semiárida do Nordeste Brasileiro (NEB) tem como principal característica as chuvas anuais baixas e irregulares (Falcão et al, 2022), com uma elevada estiagem que se reflete na paisagem, pois mesmo no período chuvoso o regime de precipitação é variável (Lira et al,2020). Recentemente Mao et al (2022) revelaram um papel dominante do Atlântico Norte tropical para déficit de precipitação e secas no NEB.…”
unclassified